Integrative Thematic Learning Model Based On Local Wisdom For Early Childhood Character - Ramdhani, Sandy (Indonesian Journal of Early Childhood Education Studies, 2019)
This research aims to: (1) produce an integrative thematic learning model based on local wisdom, (2) to know the effectiveness of integrative thematic learning model based on local wisdom in shaping the characters, mainly honesty and responsibility. This research used Research and Development design in three main stages. The research subjects were 3 teachers and three schools taken by random sampling. Research with data analysis was done statistically using MANOVA analysis. The result of the research were (1) Integrative thematic learning model based on local wisdom was developed (2) Integrative thematic learning model based on local wisdom have a good influence on the limited test or field test. (3) Integrative thematic learning model based on local wisdom in field test showed that there is significant influence on the value of honesty and responsibility characters  of children in kindergarten at Selong Sub-district, it proved by MANOVA analysis with significance value (sig.) = 0,000 at significance level 5%